Konstantina Zanou, Transnational Patriotism in the Mediterranean, 1800–1850: Stammering the Nation - Philliou, Christine M. (Historein, 2021)
Review of Konstantina Zanou. Transnational Patriotism in the Mediterranean, 1800–1850: Stammering the Nation. Oxford: Oxford University Press, 2018. 272 pp.